VIDEO EDUKASI MELALUI WHATSAPP UNTUK MENINGKATKAN PENGETAHUAN TENTANG PENCEGAHAN PENULARAN PASIEN TUBERKULOSIS - Achmad Wahdi; Moh. Alimansur; Devangga Darma Karingga; Dewi Retno Puspitosari; Erik Irham Lutfi (Jurnal LENTERA, 2026)
Tuberculosis (TB) remains a major public health concern in Indonesia, including in Kediri District, where the number of cases continues to increase. Limited knowledge among patients, families, and communities regarding TB transmission prevention contributes significantly to ongoing spread. Advances in communication technology—particularly the widespread use of WhatsApp—provide new opportunities for delivering health education in an accessible, efficient, and sustainable manner. This community service program aimed to improve tuberculosis patients’ knowledge about TB transmission prevention through direct counseling and the distribution of educational videos via WhatsApp. The intervention was conducted at Ngasem Public Health Center (Puskesmas Ngasem), involving 30 TB patients as participants. The activity included preparation, face-to-face counseling, distribution of educational videos over five consecutive days, and evaluation using pre-test and post-test questionnaires delivered online. Analysis revealed a significant increase in participants’ knowledge after the intervention, indicated by a p-value of 0.000. These results confirm the effectiveness of WhatsApp as a health education medium capable of reinforcing understanding through repeated exposure to content, clear visual explanations, and ease of access. Furthermore, WhatsApp enables flexible two-way communication between health workers and patients, supporting continuous guidance and clarification. In conclusion, WhatsApp-based video education represents an effective strategy for improving knowledge of TB transmission prevention and holds strong potential for broader and sustained implementation within community health programs.